Encyclopedia of Astrobiology - Gargaud, Muriel; Irvine, William M.; Amils, Ricardo; Cleaves II, Henderson James; Pinti, Daniele; Cernicharo Quintanilla, José; Rouan, Daniel; Spohn, Tilman; Tirard, Stéphane; Viso, Michel (Springer Berlin Heidelberg : Imprint: Springer, 2015)
The interdisciplinary field of Astrobiology constitutes a joint arena where provocative discoveries are coalescing concerning, e.g. the prevalence of exoplanets, the diversity and hardiness of life, and its increasingly likely chances for its emergence. Biologists, astrophysicists, biochemists, geoscientists and space scientists share this exciting mission of revealing the origin and commonality of life in the Universe. The members of the different disciplines are used to their own terminology and technical language. In the interdisciplinary environment many terms either have redundant meanings or are completely unfamiliar to members of other disciplines. The Encyclopedia of Astrobiology serves as the key to a common understanding. Each new or experienced researcher and graduate student in adjacent fields of astrobiology will appreciate this reference work in the quest to understand the big picture. The carefully selected group of active researchers contributing to this work and the expert field editors intend for their contributions, from an internationally comprehensive perspective, to accelerate the interdisciplinary advance of astrobiology. This new edition offers ~300 new entries. Many entries were expanded or supplemented by figures supporting the understanding of the text. Especially in the field of astrochemistry there is a huge body of new results that have been taken into account in this new edition. The synonyms and keywords have been carefully revisited. Many were added, redundant ones deleted.